SIKAP MAHASISWA TERHADAP FENOMENA BEAUTY PRIVILEGE DI LINGKUNGAN KAMPUS - Nofi Puspita Sari; Anita Aisah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Physical appearance often becomes an important aspect of social identity and plays a significant role in shaping social interactions within the university environment, giving rise to the phenomenon of beauty privilege, defined as preferential treatment received by individuals perceived as physically attractive. This study aims to explore students’ experiences and attitudes toward beauty privilege at a private university using a qualitative descriptive approach. Data were collected through in-depth interviews with 12 students who had relevant experiences with the phenomenon, and data credibility was ensured through source triangulation. The findings reveal that students perceive beauty not merely in terms of physical appearance, but also as encompassing inner qualities such as kindness, attitudes, and behavior. The presence of beauty privilege was recognized within the campus context, as reflected in differential treatment from lecturers, peers, and administrative staff toward students considered physically attractive. Nevertheless, students demonstrated critical attitudes toward this phenomenon, viewing beauty privilege as a form of social injustice that may overlook essential aspects such as competence, integrity, and personality, thereby highlighting the need for a more inclusive and equitable understanding of beauty in the university setting.